Reservoir Fish Escapement in North America: A Historical Review and Future Directions. (13th July 2022) - Lewis, Madeline C.; Cope, W. Robert; Miles, Thomas P.; Rude, Claire; Bruesewitz, Richard E.; Dodd, Benjamin J.; Flammang, Mark K.; Page, Kevin S.; Weber, Robert; Weber, Michael J.; Wolter, Max
Abstract: Downstream escapement of fishes from reservoirs via release structures can represent a loss to populations that is comparable to natural and harvest mortality. Consequently, quantifying and managing fish escapement constitute a critical component of sustainable reservoir fish management. We reviewed existing literature to assess the state of knowledge of reservoir fish escapement and found 57 unique papers published from 1942 through 2021. Early studies sought to evaluate escapement by directly capturing fish below release structures. More recently, advances in technology have enabled more detailed studies on factors influencing escapement and the influence it has on regulating reservoir fisheries. Evaluations have occurred throughout North America, assessing escapement of 49 species through a number of different outlet structures. Annual escapement estimates ranged from 0% to 100%, and escapement tended to be higher from spillways and surface release outlets compared to other outlets. Further, smaller‐bodied individuals tended to escape at higher rates than larger fish and escapement was generally positively related to reservoir discharge metrics. Sixteen papers assessed benefits of physical and nonphysical barriers for reducing reservoir fish escapement and determined that the barriers were effective for retaining fish in reservoirs. We conclude by describing management options to address escapement as well as three pressing research needs that will broaden the existing knowledge base regarding fish escapement. In light of predicted changes in precipitation events and subsequent adaptations to reservoir management, quantifying and mitigating fish escapement will be a critical component of sustainable reservoir fish management in the future.